Tyras in Late Antiquity - Oleh Saveliev (Archaeologia Polona)
The article presents materials related to the existence of Tyras in the late Roman period. Based on the available data, it is assumed that there were two phases in the existence of the city in Late Antiquity. In the first phase (second half of the 3rd to the third quarter of the 4th century AD), life in the city was restored after the barbarian raids. The Goths became the main military and political force in the steppe area of the Northwestern Black Sea region. Tyras was still receiving imported goods. However, its life was completely included in the orbit of barbarian interests. Cherniakhiv-tradition artefacts appeared in their material culture. Tyras was also receiving imported goods from Asia Minor, the Bosporus, Greece, and the Danube region. Amphoras of the Gaza type were imported in small quantities. In the second phase (last quarter of the 4th to the beginning of the 5th century AD), Tyras was still inhabited by the people who had not left the city during the Hun invasion. A few dishes of the Late Roman C / Phocaean Red Slip Ware group were delivered there, and glass dishes of Middle Eastern production and lamps with Christian symbols were used. Eastern imperial coins were in circulation. It is not known how the relations of the inhabitants of Tyras with the Huns developed. Obviously, the population was small and soon left the city forever.